1993
DOI: 10.1002/ajmg.1320450621
|View full text |Cite
|
Sign up to set email alerts
|

Holzgreve syndrome: Recurrence in sibs

Abstract: We report on 2 sibs with cardiac and renal abnormalities. The first had hypoplastic left heart sequence and renal hypoplasia; the second had a complex congenital heart defect, renal agenesis, and cleft lip and palate. We suggest that these cases represent the first familial examples of the Holzgreve syndrome. As such, they demonstrate the phenotypic variability seen in sibs, and may serve to further delineate the syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
(2 reference statements)
1
9
0
Order By: Relevance
“…This condition is a lethal multiple congenital anomalies syndrome which is probably inherited as an autosomal recessive trait. Our patient, the 4 sibs reported by Zlotogora et al [1996] and the 2 sibs reported by Thomas et al [1993] did not have polydactyly and intrabuccal bands as did the patients described by Holzgreve et al [1984] and Legius et al [1988]. This suggests that the latter cases may represent a different condition.…”
Section: To the Editorsupporting
confidence: 56%
“…This condition is a lethal multiple congenital anomalies syndrome which is probably inherited as an autosomal recessive trait. Our patient, the 4 sibs reported by Zlotogora et al [1996] and the 2 sibs reported by Thomas et al [1993] did not have polydactyly and intrabuccal bands as did the patients described by Holzgreve et al [1984] and Legius et al [1988]. This suggests that the latter cases may represent a different condition.…”
Section: To the Editorsupporting
confidence: 56%
“…It is probably inherited as an autosomal recessive trait. [4][5][6][7] Our patient was born with severe growth retardation. She had Potter face and cleft palate and soon after birth she had severe respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Leguis et al 11 made the second observation for Holzgreve syndrome. Thomas et al 4 reported two sibs with cardiac and renal abnormalities. The first baby had hypoplastic left heart and renal hypoplasia; the second baby had complex congenital heart defect, renal agenesis, and cleft lip and palate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations